Diagnosis of obstructive sleep apnea using machine learning - Sheta, Alaa; Subramanian, Shyam; Surani, Salim R.; Braik, Malik (2023 IEEE Jordan International Joint Conference on Electrical Engineering and Information Technology (JEEIT), 2023)
Sleep apnea is a sleeping disorder affecting more than 20 % of all American adults, associated with intermittent air passageway obstruction during sleep. This results in intermittent hypoxia, sympathetic activation, and an interruption of sleep with various health consequences. The diagnosis of sleep apnea traditionally involves the performance of overnight polysomnography, where oxygen, heart rate, and breathing, among other physiologic variables, are continuously monitored during sleep at a sleep center. However, these sleep studies are expensive and impose access issues, given the number of patients who need to be diagnosed. There is hence utility in having an effective triage system to screen for OSA to utilize polysomnography better. In this study, we plan to explore using several machine learning algorithms to utilize pre-screening symptoms to diagnose obstructive sleep apnea (OSA). Per our experimental results, it was found that Decision Tree Classifier (DTC) and Random Forest (RF) provided the highest classification accuracies compared to other algorithms such as Logistic Regression (LR), Support Vector Machines (SVM), Gradient Boosting Classifier (GBC), Gaussian Naive Bayes (GNB), K Neighbors Classifier (KNC), and Artificial Neural Networks (ANN).
Keywords: Artificial neural networks; Biomedical monitoring; Classification; Diagnosis; Gaussian processes; Machine learning; Machine learning algorithms; Predictive models; Sleep apnea; Sleeping disorder; Support vector machines; dept.csc